2013
DOI: 10.1177/1474515113515563
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of the EOL-ICDQ as a measure of experiences, attitudes and knowledge in end-of-life in patients living with an implantable cardioverter defibrillator

Abstract: Background Due to extended indications and resynchronization therapy, many

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 23 publications
(27 reference statements)
1
24
0
Order By: Relevance
“…The EOL-ICD Questionnaire has demonstrated sound psychometric properties. 39 In the current study, the knowledge subscale Cronbach's alpha was 0.78.…”
Section: Icd Knowledge Icd Knowledge Was Assessed Using the End-of-lmentioning
confidence: 51%
See 1 more Smart Citation
“…The EOL-ICD Questionnaire has demonstrated sound psychometric properties. 39 In the current study, the knowledge subscale Cronbach's alpha was 0.78.…”
Section: Icd Knowledge Icd Knowledge Was Assessed Using the End-of-lmentioning
confidence: 51%
“…Questionnaire. 39 The EOL-ICD is a self-rated questionnaire, consisting of three subscales that measure experiences (10 items), attitudes (18 items), and knowledge (11 items) of EOL or related issues in ICD patients. The 11 items in the knowledge subscale measure ethical aspects of treatment (3 items), how the ICD works (2 items), and the significance of ICD deactivation (6 items).…”
Section: Icd Knowledge Icd Knowledge Was Assessed Using the End-of-lmentioning
confidence: 99%
“…Instead of avoiding the subject of end of life, Thylen et al. have developed a questionnaire (EOL‐ICDQ) to help explore patients’ experiences, attitudes, and knowledge regarding end‐of‐life issues …”
Section: Discussionmentioning
confidence: 99%
“…Instead of avoiding the subject of end of life, Thylen et al have developed a questionnaire (EOL-ICDQ) to help explore patients' experiences, attitudes, and knowledge regarding end-of-life issues. 40 Pedersen, who examined patients' knowledge and wishes for information, found that 68% (n = 294) were aware of the possibility of getting their ICD deactivated and 95% believed it is important to inform patients about this option. 41 The medium age for this patient group was 58.65 ± 13.50.…”
Section: Comprehensive Understandingmentioning
confidence: 99%
“…An alternative strategy could be tailored information provided sensitively by a professional known to the patient and family at opportune times through-out device implantation. A questionnaire has been successfully implemented as such an assessment and educational tool (34). There is need for more research on the informational needs and its optimal format for patients and their family.…”
Section: Tailored Information or Event-driven Information?mentioning
confidence: 99%